GmBICs Modulate Low Blue Light-Induced Stem Elongation in Soybean - Mu, Ruolan; Lyu, Xiangguang; Ji, Ronghuan; Liu, Jun; Zhao, Tao; Li, Hongyu; Liu, Bin (Frontiers in Plant Science, 2022)
Blue-light Inhibitors of Cryptochromes (BICs) promote hypocotyl elongation by suppressing the activity of cryptochromes in Arabidopsis. Nevertheless, the roles of BICs in other plant species are still unclear. Here we investigate their functions by genetic overexpression and CRISPR/Cas9 engineered mutations targeting the six GmBIC genes in soybean. We showed that the GmBICs overexpression (GmBICs-OX) lines strongly promoted stem elongation, while the single, double and quadruple mutations in the GmBIC genes resulted in incremental dwarfing phenotypes. Furthermore, Overexpression of GmBIC2a abolished the low blue light (LBL)-induced stem elongation, demonstrating the involvement of GmBICs in regulating cryptochrome-mediated LBL-induced shade avoidance syndrome (SAS). The Gmbic1a1b2a2b quadruple mutant displayed reduced stem elongation under LBL conditions, which was reminiscent of the GmCRY1b-OX lines. Taken together, this study provided essential genetic resources for elucidating GmBICs functional mechanisms and breeding of shade-tolerant soybean cultivars in future.